Daniel Deudney, Dark Skies: Space Expansionism, Planetary Geopolitics, and the Ends of Humanity - Dal, Adnan (Uluslararası İlişkiler Konseyi Derneği İktisadi İşletmesi [EN], 2021)
Scholarly papers regarding space expansionism tend to lack an overarching perspective. To fill this gap, Daniel Deudney has penned a timely book called Dark Skies: Space Expansionism, Planetary Geopolitics, and the Ends of Humanity, which makes him a pioneering scholar in laying out a holistic approach to studying space expansionism. The book provides a comprehensive analysis of both the claims of space advocates and the consequences of space activities. Additionally, it illuminates the preeminent geographic misunderstandings about space. It examines how the completed and expected space activities of space advocates and details the orbital space and technological improvements for nuclear weapons since orbital space activities could cause a devastating nuclear war.

Scholarly papers regarding space expansionism tend to lack an overarching perspective. To fill this gap, Daniel Deudney has penned a timely book called Dark Skies: Space Expansionism, Planetary Geopolitics, and the Ends of Humanity, which makes him a pioneering scholar in laying out a holistic approach to studying space expansionism. The book provides a comprehensive analysis of both the claims of space advocates and the consequences of space activities. Additionally, it illuminates the preeminent geographic misunderstandings about space. It examines how the completed and expected space activities of space advocates and details the orbital space and technological improvements for nuclear weapons since orbital space activities could cause a devastating nuclear war.
Daniel Deudney, Dark Skies: Space Expansionism, Planetary Geopolitics, and the Ends of Humanity